Kinerja pada Karyawan Perusahaan: Apakah Dipengaruhi oleh Iklim Organisasi, Pelatihan, dan Kepemimpinan? - Permana, Ilham; Lestari, Setyani Dwi (PT Hakhara Akademia Indonesia, 2023)
The purpose of this study was to determine and analyze the effect of Organizational Climate, Training and Leadership on Employee Performance at PT. IHI Power Service Indonesia. Thisstudy uses quantitative research methods with data analysis techniques using Partial Least Square Analysis (PLS). The sample in the study used probability sampling using the simple random sampling method of 100 respondents. The data collection technique is in the form of a questionnaire. The results of the study show that organizational climate has a significant effect on employee performance, training has a significant effect on employee performance, and leadership has a significant effect on employee performance. The R square value obtained in the research was 0.638 or 63.8%. This shows that the Organizational Climate, Training and Leadership variables have a good predictive level of employee performance in research.